1979
DOI: 10.1111/j.1432-1033.1979.tb04204.x
|View full text |Cite
|
Sign up to set email alerts
|

F-Actin-Depolymerizing Activity of Human Serum

Abstract: Non‐heated human and animal sera contain a factor which exhibited an inhibiting activity on the staining of actin‐containing structures by anti‐actin antibodies in indirect immunofluoresecnce experiments. The presence of this factor lowered the viscosity of F‐actin preparations and caused, as studied by electron‐microscopy, a depolymerization of F‐actin filaments as well as inhibition of filament formation of G‐actin. The factor was, after its reaction with F‐actin, liberated seemingly unaffected, indicating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
1

Year Published

1981
1981
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(52 citation statements)
references
References 10 publications
2
49
1
Order By: Relevance
“…By contrast the ADF activity of human serum is reported to be abolished by Ca*+ chelators [2]; this may be due to an effect on factor stability rather than on the depolymerizing reaction itself.…”
Section: Discussionmentioning
confidence: 79%
“…By contrast the ADF activity of human serum is reported to be abolished by Ca*+ chelators [2]; this may be due to an effect on factor stability rather than on the depolymerizing reaction itself.…”
Section: Discussionmentioning
confidence: 79%
“…The existence of a thermolabile factor with an inhib-the same 22 AAA-positive sera in 1:160 dilution (Table 1) is strong evidence that there are no false-positive iting activity against actin-containing structures was first proposed in 1979, by Norberg et al 34 At the same results in lower dilutions in techniques D and E. This conclusion is emphasized by the absence of AAA in time, Chaponnier et al 44 characterized an actin-depolymerizing factor present in human serum. Harris et control samples from SMA-negative sera that were tested by technique D.…”
Section: Techniques Techniquesmentioning
confidence: 94%
“…Their best preparations were obtained when the polymerizing factor). 34,44 In 1982, Thorstensson et al…”
Section: Techniques Techniquesmentioning
confidence: 99%
“…The first recognized function of DBP was the plasma transport of vitamin D and other related derivatives [4]. In addition, other previous studies [5] have shown that the serum affords actin-depolymerizing activity. This property was further ascribed to the conjugate effects of gelsolin and DBP [6].…”
mentioning
confidence: 99%